Pengawasan Pemerintah Daerah Provinsi Terhadap Kapal Ikan Dan Nelayan Tradisional Di Kabupaten Kepulauan Aru - Rumra, Salahudin Alfa Rizky; Nendissa, Renny Heronia; Baranyanan, Soeleman Djaiz (Pusat Studi Hukum dan Pemerintahan Fakultas Hukum Universitas Pattimura, 2025)
This research aims to analyze the form, legal basis, and effectiveness of the supervision conducted by the Regional Government of the Aru Islands Regency over the management of traditional fisheries in coastal and local marine areas. The focus of the study is directed toward the scope of regional authority within the context of decentralization as regulated under Law Number 23 of 2014 on Regional Government and Law Number 31 of 2004 on Fisheries, as amended by Law Number 45 of 2009. The research employs a normative-juridical method, complemented by statutory, conceptual, and empirical approaches, through interviews with officials of the Department of Marine Affairs and Fisheries, field supervision officers, and traditional fishermen. The findings indicate that the authority of the Aru Islands Regency Government in supervising traditional fisheries encompasses functions of guidance, supervision, and community empowerment, as stipulated in Articles 65 and 66 of the Fisheries Law, Articles 39 to 40 of Government Regulation Number 27 of 2021, and Regulation of the Minister of Marine Affairs and Fisheries Number 48 of 2014. However, implementation remains constrained by several challenges, including limited human resources, weak inter-agency coordination, and the suboptimal role of community-based monitoring groups (Pokmaswas). This study emphasizes the importance of strengthening local supervisory institutions and integrating customary values into the governance of traditional fisheries to realize sustainable and equitable management of marine resources.